(3ecGJHI fUQ CHh GdaJhMs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd CWGd Gddg HbGAg hCOGe JCjjOg hfYeGFg hhbafG Ydjg hagefG LejY eG PcQg hMeOfG Gddg Ydi SdGeJg s
(3BNQgG (B:s
(3hbO hgH eG ajgG ef GdGdg def jbhi Ydi eWGdHJge hdG jXdege hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B92s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis